2022
DOI: 10.1186/s13052-022-01256-z
|View full text |Cite
|
Sign up to set email alerts
|

Central precocious puberty during COVID-19 pandemic and sleep disturbance: an exploratory study

Abstract: Background Increased incidence of central precocious puberty (CPP) after coronavirus infectious disease-19 lockdown has been reported. Our study aims in investigating changes in CPP rates and in sleep patterns in CPP and healthy controls. Methods CPP were retrospectively evaluated from April 2020 to April 2021. Parents of girls diagnosed with CPP during lockdown and of matched healthy controls filled out a questionnaire about sleep disturbances (SD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 35 publications
2
13
1
Order By: Relevance
“…This study did not find any differences in anthropometric parameters ( 105 ). Subsequently, other Italian groups ( 108 , 118 , 119 , 122 124 ) reported similar results. Turriziani Colonna A et al.…”
Section: Precocious Puberty During the Covid-19 Pandemic: Current Dat...supporting
confidence: 53%
See 1 more Smart Citation
“…This study did not find any differences in anthropometric parameters ( 105 ). Subsequently, other Italian groups ( 108 , 118 , 119 , 122 124 ) reported similar results. Turriziani Colonna A et al.…”
Section: Precocious Puberty During the Covid-19 Pandemic: Current Dat...supporting
confidence: 53%
“…reported a high rate (48.9%) of RPPP in females with CPP during the COVID-19 outbreak, with an increased number of children at Tanner stages 3 and 4-5 at diagnosis ( 118 ). Interestingly, another Italian group described, in subjects with CPP, a later bedtime with higher rates of sleep disturbances, such as excessive somnolence, sleep breathing disorders, and sleep–wake transition disorders ( 119 ). The collaborative Italian study by Chioma et al.…”
Section: Precocious Puberty During the Covid-19 Pandemic: Current Dat...mentioning
confidence: 99%
“…A significant increase in those newly diagnosed with CPP in the first total lockdown (March–July 2020), compared with the same period in previous years (March–July 2015-2019; 37 vs 89) were reported by Stagi et al [ 1 ], as well as by Barberi et al [ 6 ], who found a significant increase of CPP diagnosed between March 2020 and April 2021 compared with the previous 13 months. Other authors [ 2 , 4 , 5 ] reported either a total increase of 108% of girls diagnosed between March and September 2020 compared with the same period of the previous year (246 vs 118) or a 2.5-fold higher incidence rate of CPP diagnosed in 12 months (April 2020–April 2021), compared with the 3 previous years (35 vs 34). Chioma et al [ 7 ], in turn, confirmed a 1.57-fold increase in the incidence of PP, together with a general change in daily habits during COVID-19, including a reduction of physical activity, an overall greater use of electronic devices, and behavioral changes.…”
Section: Discussionmentioning
confidence: 99%
“…The Italian government imposed the national lockdown on March 9th, 2020: as of that moment, the population was compelled to stay at home. Among the consequences of this restrictive measure, it is important to point out a drastic change in children’s lifestyle, which lasted several months [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several Italian and international studies have observed that the incidence of new cases of Central Precocious Puberty (CPP) increased significantly during this period of restrictions, especially in female subjects [ 9 15 ]; moreover, the rate of pubertal progression in patients already suffering from CPP also increased compared with the rate observed in the previous years [ 10 ]. Despite several hypotheses regarding the mechanism responsible for such an increased incidence of CPP cases following the 2020 lockdown have been put forward, the real pathogenic explanation has yet to be uncovered.…”
Section: Introductionmentioning
confidence: 99%